A Manufacturing of Alternative Fashion Products and Accessories using Leftover Material at PT Seikou Seat Cover - Grace Carolline Sahertian; Lois Denissa; Wenny Anggraini; Andi Aulia Hamzah; Kezia Clarissa Langi; Fransiska Fransiska; Felicia Aurelia; Steffi Christina; Sharren Darlenne; Richelle Aurielle (Journal of Innovation and Community Engagement, 2025)
Sustainability is a practice that considers interconnectivity between humans and ecosystems in order to coexist fairly and develop in harmony for generations to come. PT Seikou Seat Cover is an automotive, seat cover, and garment company engaged in cutting and sewing for the domestic and foreign markets. This company collaborates with the Fashion Design Study Program to realize the global issue of Sustainable Development. Leftovers of synthetic leather and various fabrics of seat cover products can be reprocessed into upcycling products such as pouches, handbags, and accessories that are trendy and can be sold.  The method used is Design Exploration which is realized into alternative samples done by students and lecturers, then produced and marketed by the industry to the Generation Z community. This service has mutualistic goals and benefits, the industry can fulfill the Sustainable Development Program, by utilizing the remaining materials of its production. The Study Program can implement the learning of Fashion Studio, Sewing Patterns Studio, and Footwear Design Class to the world of work. The results of samples produced by the company are evidence of the increasing number of courses, lecturers, and student products that are utilized by the company. The results of design exploration produced by the industry serve as evidence of the increasing number of works by lecturers and students being adopted by the industry. The company can turn leftover seat covers into a sustainable business opportunity while preserving a healthy environment.